Angiogenic factors: role in esophageal cancer, a brief review - Ladeira, Kátia; Macedo, Filipa; Longatto, Adhemar; Martins, Sandra (Esophagus : official journal of the Japan Esophageal Society, 2018)
Esophageal cancer has an aggressive behavior with rapid tumor mass growth and frequently poor prognosis; it is known as one of the most fatal types of cancer worldwide. The identification of potential molecular markers that can predict the response to treatment and the prognosis of this cancer has been subject of a vast investigation in the recent years. Among several molecules, various angiogenic factors that are linked to the tumor development, growth, and invasion, such as VEGF, HGF, angiopoietin-2, IL-6, and TGF-B1, were investigated. In this paper, the authors sought to review the role of these angiogenic factors in prognosis and hypothesize how they can be used as a treatment target.